Wockhardt Limited: will it rise from the ashes?. Issue 5 (10th September 2018) - S.R., Vishwanath; Arora, Jaskiran; Prasad, Durga; Singh, Kulbir
Abstract : Synopsis: The case provides an introduction to how currency mismatches create exposures, why and how companies hedge (or do not hedge) those exposures, alternate valuation models and the use of foreign currency convertibles in funding a global expansion program. The case highlights the ambitious growth strategy of Wockhardt, a global biopharmaceutical company. In a bid to dominate the biopharmaceutical market, Wockhardt grew aggressively by acquiring companies all over the world. This expansion was funded by a mix of secured loans (bank borrowings) and unsecured loans including foreign currency (US dollar denominated) convertible bonds (FCCBs). Due to deteriorating business and economic conditions, the company experienced a sharp decline in profitability and stock price resulting in a debt overhang. The company had to restructure its capital structure in March 2009 to escape bankruptcy. Since FCCB holders did not agree to restructure the terms of the instrument, the company had to turn to senior lenders to restructure debt. The company's management is faced with several options to deal with financial distress. The case asks students to evaluate those options. The case can be used to teach hedging foreign currency exposures, design of capital structure in rapidly evolving industries and dangers of financing R&D intensive ventures with convertible debt denominated in foreign currencies. Research methodology: The case is based on secondary data sources. Information statements filed with the Securities Exchange Board of India, the company's website, press releases and security analyst reports formed the basis for this case. Supplementary information was gathered from the CAPITALINE database, and websites of the Bombay Stock Exchange and the National Stock Exchange of India. Sources of information are documented appropriately in the case and teaching note. No names in the case have been disguised. The authors have no personal relationship with the company. Relevant courses and levels: The case is suitable for courses in corporate finance, mergers and acquisitions, international financial management, corporate restructuring and valuation at the graduate level. It can also be used in executive education programs. Theoretical bases: The case provides an introduction to how currency mismatches create exposures, why and how companies hedge (or do not hedge) those exposures, alternate valuation models, the use of foreign currency convertibles in funding a global expansion program and the alternatives in corporate restructuring. Suitable references are provided in the teaching note.